2019
DOI: 10.1111/apt.15499
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir disoproxil fumarate reduces hepatocellular carcinoma, decompensation and death in chronic hepatitis B patients with cirrhosis

Abstract: Summary Background Lamivudine and entecavir reduce hepatic events and death in chronic hepatitis B (CHB) patients with cirrhosis, but the impact of tenofovir disoproxil fumarate (TDF) is less well studied. Aim To investigate the effectiveness of TDF therapy in CHB patients with cirrhosis. Methods We studied TDF‐treated and untreated CHB patients with cirrhosis from three tertiary centres. TDF cohort included consecutive patients who received TDF for ≥12 months while the untreated cohort were historical control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 27 publications
2
53
1
Order By: Relevance
“…Many reports have shown that treatments based on etiology are beneficial to improve HCC patients' prognosis. [30][31][32][33][34] In order to identify the prognostic value of the constructed model, we tested an internal cohort, and the results were consistent with those of the primary cohort. Furthermore, even when we divided the whole cohort into a 2:1 ratio, as for training and validation, the results were indistinguishable (data not shown).…”
Section: Discussionmentioning
confidence: 89%
“…Many reports have shown that treatments based on etiology are beneficial to improve HCC patients' prognosis. [30][31][32][33][34] In order to identify the prognostic value of the constructed model, we tested an internal cohort, and the results were consistent with those of the primary cohort. Furthermore, even when we divided the whole cohort into a 2:1 ratio, as for training and validation, the results were indistinguishable (data not shown).…”
Section: Discussionmentioning
confidence: 89%
“…www.nature.com/scientificreports/ Since Choi et al reported that TDF, in comparison with ETV, reduced HCC by analysing large insurance claim data and hospital cohorts 1 , subsequent studies have analysed the association between NAs and the incidence of HCC. However, they have failed to show consistent results [15][16][17][18][19][20][21][22] . Of note, a recent meta-analysis including more than 60,000 patients from 15 studies demonstrated that TDF significantly reduced the risk of HCC by 20% 23 .…”
Section: Discussionmentioning
confidence: 98%
“…This is reflected by the good performance of treated derived HCC risk scores in the absence of HBV DNA including the PAGE-B-related scores [24][25][26] and CAMD score [27,28]. The current first-line NA treatment has modified the natural history of CHB by a potent effect on HBV DNA suppression and a reduced risk of disease progression in both non-cirrhotic and cirrhotic patients [11,12,29]. The majority of treated patients can achieve complete viral suppression, i.e., undetectable serum HBV DNA, on treatment [30,31].…”
Section: Viral Load and Hcc Riskmentioning
confidence: 99%
“…They have high antiviral effects and a high genetic barrier to drug resistance [8,10]. Long-term entecavir and TDF treatment results in reduced incidence rate of HCC [11,12]. Yet HCC risk is significantly reduced but not eliminated even in patients who have achieved prolonged complete viral suppression, as genetic and/or epigenetic aberrations with malignant potentials may have already accumulated in the background liver along with long-standing HBV infection [13].…”
Section: Introductionmentioning
confidence: 99%